2018
DOI: 10.1080/10803548.2018.1524538
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects of washing and abrasion on thermal protective performance of flame-retardant fabrics

Abstract: In this study, common flame-retardant fabrics were treated with single washing or abrasion and their interactions to simulate wearing away during use. The changes in thickness, mass/m and protective performance of the fabrics under both flame and radiation environments were evaluated. Results demonstrated that the protective performance was firstly increased after washing or abrasion, and then decreased with further increasing washing or abrasion cycles. After certain treatment cycles, the combined effect of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…, 2013; Chen et al. , 2003; Wang et al. , 2021), smart fabrics and clothing with sensing or monitoring functions (Wu et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2013; Chen et al. , 2003; Wang et al. , 2021), smart fabrics and clothing with sensing or monitoring functions (Wu et al.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it had the strongest bursts of 29.04 during 2013-2021, which also evidenced the rapid growth. In terms of research focuses, Donghua University had extensive research on waterproof and breathable nanomaterials (Li et al, 2015;Sheng et al, 2017;Ge et al, 2013), thermal comfort and thermal protection of clothing (Lu et al, 2013;Chen et al, 2003;Wang et al, 2021), smart fabrics and clothing with sensing or monitoring functions (Wu et al, 2019;Guo et al, 2018). Institutions from domestic and overseas have been constantly working with Donghua University on those topics, for instance, Hong Kong Polytechnic University and Chinese Academy of Sciences in China, the University of Alberta in Canada, Cornell University and University of Georgia in the USA, Lund University in Sweden, Yonsei University in South Korea and Deacon University in Australia, etc.…”
mentioning
confidence: 99%
“…However, with further increasing the friction cycles to the maximum level of 800 in F800, t 2nd and t 3rd were raised back to the original level as in the untreated state, which were found to be significantly higher than those in F200 and F400 (p < .05). Previous studies have shown that the thickness of the aramid fabric increased with the cycles of daily abrasion simulations, such as washing and friction, because of fuzzing occurrence on the fabric surface (Kutlu & Cireli, 2005;Wang et al, 2021). A possible explanation for this enhanced thermal protection is that the 800 cycles of friction greatly increased the thickness of the outer shell layer (i.e., 0.57 mm), increasing its ability to hold still air within the fabric layer and improving the t 2nd and t 3rd .…”
Section: Effects Of Frictional Abrasion Onlymentioning
confidence: 99%
“…They found that the surface wetting rate of fabrics and their liquid penetration was reduced due to abrasion treatments. Wang et al (2021) examined effects of abrasion on the degradation of physical and protective properties for firefighters' protective clothing under exposure to flame and radiant heat. The results showed that the thickness of the fabric increased with abrasion cycles, while fabric mass and thermal protective performance increased initially and then decreased with an increasing of abrasion cycles.…”
mentioning
confidence: 99%
“…A plenty of studies had been performed to investigate the accelerated aging on mechanical strength of thermal protective fabrics. The aging method included ultraviolet light exposure (Houshyar et al, 2018), thermal exposure (Barker and Lee, 1987), washing and abrasion (Wang et al, 2018), etc. Considering the nature of occupational situations of firefighters, the studies on thermal protective clothing field focused on the effects of thermal exposures (Rezazadeh, 2014).…”
Section: Introductionmentioning
confidence: 99%